KEKUASAAN MEDIA TELEVISI KOMERSIAL DAN NETRALITAS INFORMASI - S. Arifianto (Jurnal Studi Komunikasi dan Media, 2011)
Writing this paper departs from the emergence of the phenomenon of the use of economic interests and political power in the media content of commercial television in Indonesia by its owner. In relationship to the background, review papers focused on issues of media power commercial television and its relation to the neutrality of information. Concept used to analyze these problems are the theory of political economy of media and media impartiality. Material obtained from the analysis of literature studies, documentation, and media clippings. The results of the discussion showed that the commercial television media editorship neutrality difficult to maintain because it is contaminated by the power of the owner. This contamination has implications on the number of commercial television media to be ambivalence. This condition tends to worsen the image of an operational commercial television. In this context the medium of television can be used for the fulfillment of economic and political interests of media owners based on power. Penulisan paper ini berangkat dari munculnya fenomena penggunaan kepentingan ekonomi dan politik kekuasaan dalam pemediaan konten televisi komersial di Indonesia oleh pemiliknya.  Dalam hubungan latar belakang tersebut, telaah paper difokuskan pada persoalan kekuasan media televisi komersial dan relasinya terhadap netralitas informasi. Konsep yang digunakan untuk menganalisis permasalahan tersebut adalah teori ekonomi politik media dan imparsialitas media. Bahan analisis diperoleh dari hasil studi literatur, dokumentasi, dan kliping media. Hasil bahasan menunjukkan bahwa netralitas keredaksian media televisi komersial sulit dipertahankan karena terkontaminasi oleh kekuasaan pemilik. Kontaminasi ini berimplikasi pada banyaknya media televisi komersial yang bersikap ambivalensi. Kondisi ini cenderung memperburuk citra televisi komersial yang beroperasional. Dalam konteks ini media televisi dapat digunakan untuk pemenuhan kepentingan ekonomi dan politik dari pemilik media berdasarkan kakuasaan